Implementasi Alat Pembatas Kecepatan Di Kecamatan Binawidya - Rohmawati Rohmawati; Febri Yuliani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Road is a land transportation insfrastucture that covers all part of the road, including traffic facilities. One of the most common road equipment facilities is speed limiters which function to limit the speed of vehicle users. The regulation that governing about these speed limiters are Regulation of Minister of Transportation Number 14 of 2021. This policy was made as a guideline for the implementation of road equipment facilities, including speed limiters. However, in its implementation in Binawidya District, this regulation is rarely known by the public. In the end, many road that require this tool were built independently, without knowing the actual shape and size. The organizer of this regulation for city road is the Mayor, who is assisted by the City Transportation Agency. This research uses a qualitative method and using Malcolm L.Goggin, et al. theory of policy implementation as a reference. The result show that the implementation of these policies is still not optimalized. There are three factors that hinder it, and that is 1) there no separate Regional Regulation regarding speed limiting device, 2) the lack of communication and socialization through social media that are ineffective, and 3) the human resource who understand the technical work of speed limiting device are still lacking..